2010
DOI: 10.3113/fai.2010.0807
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Analysis of Metatarsus Primus Elevatus and Hallux Rigidus

Abstract: Based on the findings in this study, an MPE greater than 5 mm could be considered a predictive factor in the presence of hallux rigidus. However, the mechanism of MPE has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 24 publications
0
37
1
Order By: Relevance
“…Espinosa et al [17] demonstrated a significant 5.2 mm elevation of the first metatarsal in patients with hallux rigidus compared with hallux valgus and controls in a 295 ft study. In these latter two groups of patients, the position of the first metatarsal was at 2.8 and 2.6 mm of elevation from the second metatarsal, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Espinosa et al [17] demonstrated a significant 5.2 mm elevation of the first metatarsal in patients with hallux rigidus compared with hallux valgus and controls in a 295 ft study. In these latter two groups of patients, the position of the first metatarsal was at 2.8 and 2.6 mm of elevation from the second metatarsal, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The phalangeal reference points in the anteroposterior and lateral radiographs were placed 0.5 to 1 cm distal to the proximal articular surface and 0.5 to 1 cm proximal to the distal articular surface or the tip of distal phalanx (18). Metatarsus primus elevatus was measured using the method described by Bouaicha et al (18) (Fig. 1).…”
Section: Radiographic Evaluationsmentioning
confidence: 99%
“…The proximal metatarsal reference points in the lateral radiographs were placed 1 to 2 cm distal to the proximal articular surface and the distal points were placed on the center of the approximate circle fit in the metatarsal head. The phalangeal reference points in the anteroposterior and lateral radiographs were placed 0.5 to 1 cm distal to the proximal articular surface and 0.5 to 1 cm proximal to the distal articular surface or the tip of distal phalanx (18). Metatarsus primus elevatus was measured using the method described by Bouaicha et al (18) (Fig.…”
Section: Radiographic Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, a decrease or absence of range of motion, along with pain and/or crepitus, is noted (2). Radiographically, typical joint destructive changes are identified, including narrowing and flattening of the joint space, subchondral sclerosis, cystic changes, joint debris, and dorsal spurring (2,3). Intraoperatively, a direct examination of the joint surfaces reveals denudation of cartilage, cystic changes to the surrounding bone, and periarticular osteophytic spurring.…”
mentioning
confidence: 99%